VERBAL ABUSE IN UPBRINGING AS THE CAUSE OF LOW SELF-ESTEEM IN CHILDREN - Mackowicz, Jolanta (European Scientific Journal, ESJ, 2014)
In this article I would like to raise the issue of verbal child abuse in relationships between children and people important to them. Parents and teachers are the first role models in a child’s life, therefore their messages have a causative power as they create the image of the “self” in a child, as well as the way of perceiving and valuing themselves. The starting point of my article is the issue of abuse in upbringing, then I discuss the problems of selfesteem and the occurrence of verbal abuse by parents and teachers. In the last part, I present consequences of such experience for the development and life of children.